Intracavitary physiotherapy combined with acupuncture mediated AMPK/mTOR signalling to improve endometrial receptivity in patients with thin endometrium. (October 2022) - Qi, Yinghua; Wang, Xiaoxuan; Hou, Sen; Wu, Zhijuan; Xu, Xiaoyan; Pang, Conghui
Abstract: Objective: To explore the mechanism of intracavitary physiotherapy combined with acupuncture to improve the receptivity of thin endometrium. Methods: From October 2020 to April 2021, 40 patients diagnosed with thin endometrium and preparing for hormone replacement cycle freeze–thaw embryo transfer in our centre for Reproduction were included, 40 patients were randomized to treatment group and control group. 20 patients with normal endometrium during the same period were selected as the normal group.All patients underwent freeze–thaw embryo transfer using hormone replacement cycles.The treatment group added endovascular physiotherapy combined with acupuncture. Results: The endometrial receptivity of the patients with thin endometrium was significantly lower than that of the normal group( P < 0.01). Endovascular therapy combined with acupuncture can significantly increase endometrial thickness in patients with thin endometrium and the proportion of patients with type A endometrium, reduce bilateral Uterine arterial pulsatility index (PI), Uterine arterial resistance index (RI), and peak systolic velocity/diastolic velocity (S/D), upregulate the expression of HOXA10 protein and mRNA in endometrium tissue, and improve the rate of embryo implantation and clinical pregnancy( P < 0.01).there was no significant difference between the treatment group and the normal group ( P > 0.05). This may be related to the regulation of the AMPK/mTOR signalling pathway by intracavitary physiotherapy combined with acupuncture, downregulation of the expression of the AMPK gene and protein and upregulation of the expression of the mTOR gene and protein. Conclusions: 1. Abnormal energy metabolism is present in the endometrium of patients with thin endometrium, which affects the autophagy process and leads to a decrease in the receptivity of thin endometrium. 2. Intracavitary physiotherapy combined with acupuncture mediated the AMPK/mTOR pathway to improve energy metabolism, promote the autophagy process, improve endometrial morphology and ultrasonic indicators of patients, upregulate the expression of endometrial receptivity-related HOXA10 genes and proteins, and improve the embryo implantation rate and clinical pregnancy rate.